TEACHING ENTREPRENEURSHIP IN THE ETHICAL-POLITICAL DIMENSIONS OF UNDERGRADUATE NURSING CURRICULA IN NORTHEASTERN BRAZIL - Luis Fernando Reis Macedo; Maria Neyze Martins Fernandes; Thais Rodrigues de Albuquerque; Antonio Germane Alves Pinto; Ticiana Maria Gomes Guedes de Matos; Jackeline Kérollen Duarte de Sales; Kenya Waléria de Siqueira Coelho Lisboa (Universidade Federal do Paraná, 2024)
Objective: to analyze the approach to content related to entrepreneurship in the ethical-political dimensions in curricular documents of undergraduate nursing courses. Method: documentary research, with a mixed approach and descriptive nature, from June 2021 to August 2022, with inspection of the Ministry of Education's website, of the institutions offering Nursing courses in the Northeast region of Brazil. Content and quantitative evaluation using the T-test. Results: the majority of HEIs offered face-to-face courses (94.1%) and belonged to private institutions (64.7%). The subjects mainly covered theoretical topics (94.1%), highlighting the importance of entrepreneurship in the training of nurses. The lexicographic and similarity analysis highlighted the strong link between the words "Entrepreneur" and "Health", highlighting the relevance of these concepts in the training of nurses. Conclusion: The curriculum documents highlight the importance of training nurses in their professional and entrepreneurial roles with competence, taking into account the principles of Bioethics, Morals, Science, and Philosophy.